Common Genetic Variants in miR-1206 (8q24.2) and miR-612 (11q13.3) Affect Biogenesis of Mature miRNA Forms - Kim, Hye Kyung (Public Library of Science, 2012)
Cancer genome-wide association studies (GWAS) have identified many common genetic markers located in non-coding regions of the genome. Two notable examples are the multi-cancer susceptibility regions, 8q24.2 and 11q13.3. Since these GWAS signals localize to gene-poor regions, we investigated genetic variants within pre-microRNA (pre-miRNA) transcripts as a possible link between the GWAS findings and the associated molecular phenotypes. Across the two regions, which contain 37 miRNAs genes, we explored genetic variants by surveying public databases and conducting targeted resequencing. Specifically, we investigated one common single nucleotide polymorphism (SNP) within miR-1206 on 8q24.2 and two SNPs within miR-612 on 11q13.3. Though these variants are not correlated with known GWAS signals, we conjectured that they might be important for function of corresponding miRNAs. To test the functional significance of these genetic variants, we cloned both allelic forms of miR-1206 and miR-612 pre-miRNA into expression vectors and assessed biogenesis of mature miRNA-forms. The two SNPs within miR-612 significantly affected expression of mature miR-612 in a cell-type specific manner; enhancement in prostate cancer cell lines, reduction in colon cancer cells, and no effect in breast cancer cell lines. The SNP within miR-1206 also affected expression of mature miR-1206, but not in a cell-type specific manner. Future studies should identify targets of miR-1206 and miR-612 and help understand the biological roles of these miRNAs and their possible role in carcinogenesis.